2015
DOI: 10.1002/pd.4609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating first trimester maternal serum screening combinations for Down syndrome suitable for use with reflexive secondary screening via sequencing of cell free DNA: high detection with low rates of invasive procedures

Abstract: First trimester reflexive testing does not require nuchal translucency measurements, and has high detection and very low rates of invasive procedures. However, timing of DNA sample collection and the costs of sample collection and DNA testing need to be considered before implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
(108 reference statements)
2
16
0
Order By: Relevance
“…First trimester maternal serum free β‐hCG levels in OSB have been reported to be reduced in two series, and a published model found that adding both AFP and free β‐hCG to BPD MoM based on CRL increased detection from 50% to 58% for a 5% false‐positive rate . When screening for Down's syndrome in the first trimester, performance can be enhanced by the addition of maternal serum AFP, with or without PlGF . Centres using such protocols will be able to take advantage of the AFP measurement to achieve improved OSB detection.…”
Section: Discussionmentioning
confidence: 99%
“…First trimester maternal serum free β‐hCG levels in OSB have been reported to be reduced in two series, and a published model found that adding both AFP and free β‐hCG to BPD MoM based on CRL increased detection from 50% to 58% for a 5% false‐positive rate . When screening for Down's syndrome in the first trimester, performance can be enhanced by the addition of maternal serum AFP, with or without PlGF . Centres using such protocols will be able to take advantage of the AFP measurement to achieve improved OSB detection.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of the screening performance of reflex DNA screening for Down syndrome has been previously described . Briefly, two million Down syndrome and two million unaffected pregnancies were simulated, each with a set of ultrasound and serum marker values and a maternal age based on published screening marker parameters and the maternal age distribution of England and Wales 2006 to 2008 . For each simulated pregnancy and each disorder, an initial test risk was calculated, by multiplying the maternal age specific odds of having an affected live birth by the likelihood ratio of the pregnancy being affected (for the simulated set of marker values), which were calculated from the multivariate Gaussian distributions of combinations of NT, DVPI, free β ‐hCG, PAPP‐A, AFP, inhibin‐A and PlGF levels, and the presence or absence of fetal nasal bone in affected and unaffected pregnancies .…”
Section: Methodsmentioning
confidence: 99%
“…It can also be improved by enhancing the screening performance of the initial screening test used to determine which women have a reflex DNA test. This can be performed by adding markers to the conventional Combined test . We here estimate the effect of enhancing the initial first trimester test for Down syndrome by adding the biochemical markers placental growth factor (PlGF), inhibin‐A, and AFP and the ultrasound markers ductus venosus pulsality index (DVPI) and fetal nasal bone examination (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centers currently using a version of the combined test enhanced by the addition of nasal bone determination will have higher marginal costs when changing protocol because the detection rate advantage of cfDNA testing is smaller. Those currently using a version of the combined test enhanced by additional maternal serum markers, placental growth factor and AFP will need fewer additional funds but will have higher marginal costs.…”
Section: Model‐predicted Proportion Of Down‐syndrome Cases Detected Amentioning
confidence: 99%